2022
DOI: 10.1186/s12903-022-02168-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus: comparative efficacy and treatment costs—a systematic review

Abstract: Objective To compare the reported efficacy and costs of available interventions used for the management of oral lichen planus (OLP). Materials and methods A systematic literature search was performed from database inception until March 2021 in MEDLINE via PubMed and the Cochrane library following PRISMA guidelines. Only randomized controlled trials (RCT) comparing an active intervention with placebo or different active interventions for OLP managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…On the one hand, PDT was reported as more effective over dexamethasone mouthwash (70); on the other hand, dexamethasone mouthwash showed a better effectiveness in comparison to PDT (84). Furthermore, two other studies showed a similar efficacy of PDT in comparison to dexamethasone mouthwash and triamcinolone paste 0.1% (71). In comparison to LLL, PDT was more effective in a study conducted on 45 OLP patients (70).…”
Section: Photodynamic Therapymentioning
confidence: 79%
See 2 more Smart Citations
“…On the one hand, PDT was reported as more effective over dexamethasone mouthwash (70); on the other hand, dexamethasone mouthwash showed a better effectiveness in comparison to PDT (84). Furthermore, two other studies showed a similar efficacy of PDT in comparison to dexamethasone mouthwash and triamcinolone paste 0.1% (71). In comparison to LLL, PDT was more effective in a study conducted on 45 OLP patients (70).…”
Section: Photodynamic Therapymentioning
confidence: 79%
“…Indeed, in one study on 34 OLP patients, clobetasol gel 0.05% was more effective than LLL, while, in another one on 42 OLP patients, LLL showed a better effectiveness in comparison to clobetasol gel 0.05% (71,72). Furthermore, dexamethasone solution and triamcinolone paste 0.1% showed higher efficacy than LLL (71,73). The positive effects of LLL on erosions and ulcerations in OLP could be explained by its biological activity on different cells, such as fibroblasts and epithelial cells, which play a pivotal role in the wound healing process (72).…”
Section: Lasersmentioning
confidence: 97%
See 1 more Smart Citation
“…The non-erosive type is clinically characterized by white streaks (Wickham´s striae), white plaques, and erythematous lesions, while the erosive type shows multiple painful erosions and ulcerations without well-defined borders and a necrotic base, that impair the quality of life of the patients ( 1 , 2 ). Moreover, non-erosive OLP is usually asymptomatic and mostly responsive to topical therapies with corticosteroid or calcineurin inhibitors ( 3 ). By contrast, the therapy of erosive OLP is extremely tricky.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the therapy of erosive OLP is extremely tricky. Indeed, topical therapies are usually ineffective and patients need systemic therapies, which are mostly off-label, including methotrexate, hydroxychloroquine, and interleukin (IL) antagonists, such as guselkumab (anti-IL23 agent) or secukinumab (anti-IL 17 agent) ( 3 , 4 ). In addition, in erosive OLP a malignant transformation has been reported in up to 5% of the patients ( 5 ).…”
Section: Introductionmentioning
confidence: 99%